Hubungan Bilateral Indonesia-Tiongkok dalam Mewujudkan Kereta Cepat Pertama di Asia Tenggara dan Penyebab Sebenarnya Penanggungan Utang Oleh APBN Sejak Terjadi Cost Overrun - Rafianda, Azhar Farel; Molana, Wisesa Syauqi; Kurniawan, Yeri; Mardiansyah, Farhan Bagus (TRANSBORDERS: International Relations Journal, 2024)
As can be seen from the extensive bilateral cooperation between Indonesia and China since President Joko Widodo took office in 2014, this opportunity has had a relatively large and intense impact in both positive and negative forms. Of all the forms of cooperation that have been implemented by these two countries over time, one project that is currently attracting the attention of many people in Indonesia-China relations is the construction of the Jakarta-Bandung High Speed ​​Train by the KCIC joint venture. This project faces various challenges, but what will be the main benchmark for the discussion now will be seen from the biggest issue during the middle to the end of the project's progress, namely cost overruns. This type of debt raises quite some worrying problems for the Indonesian budget due to the failure of paying in full only from their main business method, which is business to business (B2B) by the consortium of each respective national banks and companies from the two countries that funded the KCIC project. Because it can no longer be borne by these investors alone, the Indonesian government must step in by providing debt guarantees using its national budget or APBN, which currently also covers a lot of debt from other major projects. It is necessary to clarify again what the causes of this cost overrun are based on the development flow of the KCIC project and consider internal and external aspects that can be used as a reference in finding a definitive answer in pinpointing the source of the problem. Because the risk of using Indonesia's own national budget for large-scale projects can have serious implications for the state’s integrity as a whole.